Exceptions of banking secrets for the interest of taxes in Indonesia (a comparison of the post-birth of access law to financial information) - Mutiara, Upik; Simanjuntak, Ika Khairunnisa; Hasibuan, Rahmad Ramadhan; Amiludin, Amiludin (Legality : Jurnal Ilmiah Hukum, 2020)
Act Number 7 of 1992 as amended by Act Number 10 of 1998 concerning Banking and several related rules already regulates the exclusion of banking secrets, especially for tax purposes. However, the existing mechanism has not been able to accommodate the exchange of financial information within the framework of the Automatic Exchange of Information (AEOI). Then the Financial Information Access Act was formulated which regulates the automatic exchange of financial information that has never been known before. The problems discussed in this study, how are the exceptions of bank secrets for tax purposes that have been carried out in Indonesia and how are bank secrets exceptions regulated in the Financial Information Access Act. The research method used is a normative juridical method with a descriptive-analytical research approach. The results of the study found that the exception of bank secrets has long been known in Indonesia but is still limited by a convoluted bureaucracy. Whereas in the Financial Information Access Act, exceptions take place automatically but there are sanctions for those who misuse information.